The Expression of Sound Art in Piano Performance - Luo, Gaofeng; Ning, Yudan; Zong, Liang (Journal of Education and Educational Technologies, 2023)
For piano performers, they should apply extensive literary cultivation, conduct in-depth research and understanding of musical works, and then play touching melodies through reasonable playing methods, allowing both the audience and the performer to experience pleasure and generate some associations and imagination, thus realizing the emotions and philosophies that the composer wants to express in music, and achieving the goal of cultivating sentiment. n this essay an attempt has been made to consider the English novel historically. Its principle aim, however, is to help us, English majors, to become more aware of the variety of the novel as a form of literature, of the pleasure it has to offer, and of the interpretative skills which a careful reading of novels may help to develop. Through the general recognition of novels, especially British novels, English majors may have a systematical study, which will make their study more effectively.